Do sport teams with greater team resilience perceive higher performance at the end of the season? A multilevel analysis - López-Gajardo, M. A.; McEwan, D.; Pulido, J. J.; Díaz-García, J.; Leo, F. M. (Scandinavian Journal of Medicine & Science in Sports, 2022)
A team's ability to respond positively to adversities, problems, and obstacles during their season is an essential part of success in collective sports. Grounded in team resilience theory and using a multilevel analytical approach, this study examined the relationship of the characteristics of resilience and vulnerability under pressure with perceived individual and team performance. Participants were 676 soccer players (530 males and 146 females) aged 15-42 years (M = 21.40, SD = 5.38), who played on 64 senior and under-18 soccer teams of several national leagues in Spain. In the final month of the season, factors related to team resilience and individual and team performance were analyzed. We estimated multilevel models by including perceived individual and team performance as dependent variables. Characteristics of resilience and vulnerability under pressure were considered as fixed and random effects (i.e., individual- and team-level intercepts and slopes). At the individual level, results showed that characteristics of resilience were positively associated with subjective individual and team performance, whereas vulnerability under pressure was negatively related to perceived team (but not individual) performance. At the team level, only characteristics of resilience positively predicted team performance. These findings suggest that more resilient teams report more successful performance from an individual and team perspective, whereas teams that are more vulnerable under pressure report poorer team performance. Taken together, the study underscores the importance of practitioners to develop strategies that improve their teams' resilience, given that team resilience helps to achieve positive subjective individual and team outcomes.